Fatigue mechanisms and energy shuttles in intermittent high intensity activity - Maile, A. (1998)
Effective energy provision will result from the implementation of integrated and effective work/rest ratios, which delay the onset of fatigue, facilitate effective recovery and, perhaps more importantly, eradicate the potential problems associated with overtraining. The 'shuttle' systems of creatine kinase, adenylate kinase, nicotinamide adenine dinucleotide and lactate dehydrogenase need to be stimulated by the organisation, design and prescription of relevant training methods. Training effectiveness will therefore be improved by a better understanding of metabolic limitations supported by physiological assessment, which means that training can be made more specific.